APLIKASI AKUNTANSI DEPOSITO MUDARABAH PADA LEMBAGA KEUANGAN SYARIAH NON BANK DI BANJARMASIN - Hariyanto Hariyanto (Islamic Economics and Business Faculty of UIN Antasari, 2014)
this research aims to know the application of PSAK accounting 101 about Islamic finance report and PSAK NO. 105 of mudarabah to product depositing mudarabah in an exemplary KJKS Banjarmasin and Independent Companions Banjarmasin, UJKS and constraints encountered in the recording of accounting. This research is qualitative research interview method and documentation. This type of research is the research field (field research). Through qualitative descriptive analysis techniques. This research resulted in the application of accounting deposits mudaraba based on PSAK NO. 105. KJKS Example already implement thoroughly on the rules contained in the financial reports of 101 PSAK syariah and PSAK NO. 105 temporary syirkah funds of mudaraba, while Independent Companions UJKS not yet fully apply PSAK NO. 101 and PSAK NO. 105. While the obstacles faced in recording accounting mudaraba deposits i.e. HR lack of knowledge about the Islamic accounting and the lack of number of employees in the finance or accounting